Infected Pseudoaneurysm in a Tertiary Centre: A Retrospective Audit - DS, Sanjay; Dhayalan, G; MNA, Abdul Rahman; F, Othman (IIUM Medical Journal Malaysia, 2020)
Introduction: Infected pseudoaneurysms among intravenous drug abusers are a serious clinical condition that carries significant morbidity and mortality. The management of such cases has been controversial on deciding the need of revascularisation following simple ligation and local debridement. In this audit, we present the results of simple ligation and local debridement of our patients with infected pseudoaneurysm. Materials and methods: We conducted a retrospective review from 2013 to 2018 on 15 of our patients who are intravenous drug abusers that underwent simple ligation and local debridement for an infected pseudoaneurysm. Results: All 15 patients underwent simple ligation and local debridement. They were all male patients, and majority of the patients were between group ages of 30-40 years old at 66.7%. The oldest patient was 63 years old. All the patients self-injected the affected site for a minimum duration of 36 months. 73% of the patients had femoral pseudoaneurysm, making it the most common affected site in our audit. The remaining patients had axillary and radial pseudoaneurysm and none of our patients had brachial pseudoaneurysms. Majority of our patients were underlying Hepatitis C at 46.7%, 2 of our patients were HIV positive and only one had Hepatitis B. The remaining 5 patients’ statuses were unknown. In accessing the complications, two patients had re-bleeding after the procedure and were eventually discharged well and were uneventful. One patient required amputation as he developed a gangrenous limb within the same admission after ligation and excision of the infected pseudoaneurysm. There were two deaths due to sepsis with multiorgan failure. 10 patients were discharged well without any complications after surgery. Conclusion: Infected pseudoaneurysms can be safely managed with simple ligation and local debridement without revascularisation as they pose acceptable complication rates.